Integrated Network Pharmacology and Comprehensive Bioinformatics Identifying the Mechanisms and Molecular Targets of Yizhiqingxin Formula for Treatment of Comorbidity With Alzheimer’s Disease and Depression - Zhang, Tingting; Wei, Wei; Chang, Surui; Liu, Nanyang; Li, Hao (Frontiers in Pharmacology, 2022)
Background: The Yizhiqinxin formula (YZQX) has been used to treat Alzheimer’s disease (AD) or major depression disorder (MDD). However, its specific underlying mechanisms and therapeutic targets remain unclear. Methods: The ingredients and putative targets of YZQX were screened using the TCMSP and Drugbank databases. Next, the GEO databases were used to retrieve relevant differentially expressed genes (DEGs) in AD or MDD and normal tissues. The PPI network was established, merged, and further screened to identify the main ingredients and core targets of YZQX against AD and MDD comorbidities. We performed enrichment analysis of core targets to identify the biological processes and pathways. Finally, AutoDock software was used to validate the binding affinity between the crucial targets of direct action and their corresponding ingredients. Results: A total of 43 ingredients were identified from YZQX, of which 43 were screened to yield 504 targets. By establishing the PPI network, 92 targets were regarded as targets of YZQX against AD and MDD comorbidities in the core network. Promising targets (HSP90AA1, ESR1, AKT1, VCAM1, EGFR, CDK1, MAPK1, CDK2, MYC, HSPB1, and HSPA5) and signalling pathways (PI3K-Akt signalling pathway, ubiquitin mediated proteolysis, MAPK signalling pathway, etc.) were filtered and refined to elucidate the underlying mechanism of YZQX against AD and MDD comorbidities. Molecular docking confirmed that the ingredients of YZQX (quercetin and kaempferol) could bind well to multiple crucial targets. Conclusions: The ingredients of YZQX, such as quercetin and kaempferol, might treat AD and MDD comorbidities by acting on multiple targets and pathways.